Scanning-tunneling microscopy/spectroscopy and break-junction tunneling spectroscopy of FeSe1-xTex - Ekino, T.; Sugimoto, A.; Gabovich, A.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The iron-chalcogenide superconductor FeSe1–xTex (0.5 < x < 1) was investigated by scanning-tunneling microscopy/spectroscopy (STM/STS) and break-junction techniques. In the STM topography of the samples, randomly distributed Te and Se surface atomic structure patterns correlate well with the bulk composition, demonstrating that nanoscale surface features directly reflect bulk properties. The high-bias STS measurements clarified the gap-like structure at ≈ 100–300 meV, which is consistent with the break-junction data. These highenergy structures were also found in sulfur substituted FeS0.1Te0.9. Possible origin of such spectral peculiarities is discussed. The superconducting gap 2Δ ≈ 3.4 ± 0.2 meV at temperature T = 4.2 K was found in the break junction of FeSe1–xTex with the critical temperature Tc ≈ 10 K. The corresponding characteristic gap to Tc ratio 2Δ/kBTc ≈ 4 ± 0.2 indicates moderate superconducting coupling (kB is the Boltzmann constant).